A formação continuada de professores e o trabalho pedagógico - Buffon, Elciana (2017)
The Continuing Teacher Education represents an important mean in the teacher’s education and consequently to the quality of education. It also comprehends a process of study, reflections and knowledge building. The goal of this dissertation is to analyse the process of continuing education of Physical Education teachers that work in the municipal network of Santa Maria, RS, in the period of 2011 to 2016. Our specific goals are: establish a relation between teachers’ practice and education; analyse the continuing education process and its implications in the practice of Physical Education teachers in this period. An exploratory study was made to understand the area of interest from the 39 continuing education meetings. The documents used were: the reports, audio and video from the meetings, the questionnaire and the semi-structured interview made with a teacher. We found that the the teachers’ job goes beyond school borders, and it demands proper time and space. Regarding the continuing education, we inferred that it provided important moments when the teacher was able to reflect and rethink his/her own work. We conclude that the implications of the continuing education on the teacher’s job has had great benefits so far, among them: the reorganisation of the timetable to comprise planning and continuing education, collective construction of the city’s curricular guidelines, and from this document, the organisation of an event for teachers and professors of the network. However, the guarantee of specific time (outside planning period) for continuing education is still under initial discussion, a time that contributes, even in small proportions, to the quality of education. Finally, we emphasise the importance of the triad school, university and secretary of education to reduce the distances and advance the discussions on the field.